2014
DOI: 10.1111/bju.12666
|View full text |Cite
|
Sign up to set email alerts
|

Oncological predictive value of the 2004 World Health Organisation grading classification in primary T1 non‐muscle‐invasive bladder cancer. A step forward or back?

Abstract: ObjectiveTo compare the clinical reliability of the 1973 and 2004 World Health Organisation (WHO) classification systems in pT1 bladder cancer. Patients and MethodsWe retrospectively evaluated 291 consecutive patients who had pT1 high grade bladder cancer between 2004 and 2011. All tumours were simultaneously evaluated by a single uro-pathologist as high grade and G2 or G3. All patients underwent a second transurethral resection (TUR) and those confirmed with non-muscle-invasive bladder cancer at second TUR re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 26 publications
1
33
0
1
Order By: Relevance
“…The present findings in a large population among four academic hospitals confirm the ineffectiveness of the WHO2004 classification in T1‐BC. On the contrary, WHO1973 has been reported a prognosticator for progression and CSS in several larger T1‐BC cohorts ( n = 166–587) . These included only one comparative study by Otto et al , who, as previously mentioned, did not find the WHO2004 system to be of prognostic value.…”
Section: Discussionmentioning
confidence: 97%
“…The present findings in a large population among four academic hospitals confirm the ineffectiveness of the WHO2004 classification in T1‐BC. On the contrary, WHO1973 has been reported a prognosticator for progression and CSS in several larger T1‐BC cohorts ( n = 166–587) . These included only one comparative study by Otto et al , who, as previously mentioned, did not find the WHO2004 system to be of prognostic value.…”
Section: Discussionmentioning
confidence: 97%
“…The newer classification system has been around for more than a decade and publications evaluating its longer term validity are somewhat scarce, to our knowledge, but nonetheless deemed reliable [9]. The 2004 classification system is still being recommended to be used alongside the 1973 system as best practice, despite a recent (2016) update of the classification system [15] and some recent evidence in favour of the 1973 classification system in pT1 cancers [16]. It must be noted that the 2004 system has not been used in any prognostic risk-models to date [9].…”
Section: Discussionmentioning
confidence: 99%
“…Equally, the 2004 system appeared to be more representative of the tumour natural history in relation to progression. Cao and colleagues [26] demonstrated that the 2004 classification system predicted recurrence and progression better than the 1973 system, particularly in noninvasive tumours, while Otto et al [27] and Pelluchi et al [16] revealed that the 1973 classification system was better in pT1 cancers regarding the prediction of progression. In addition, Burger et al revealed that the 2004 system was more accurate in predicting recurrence in patients with regular onset bladder cancer compared to those with the early onset bladder cancer (> 45 years of age) [28].…”
Section: Prediction Of Recurrence and Progressionmentioning
confidence: 99%
“…The previous system acknowledges the morphological spectrum of tumour grade, and Pellucchi et al . demonstrated that application of the 1973 grading system can stratify patients with lamina propria invasion . Recurrence‐free and progression‐free survival were significantly worse in the grade 3 group compared to the grade 2 group.…”
Section: Stage Pt1 Carcinomamentioning
confidence: 98%